From Participation to Critical Thinking: The Role of a Mind Map-Based Constructive Collaborative Approach in Learning the Human Reproductive System - Najwa Syahrani; Adi Rahmat; Eni Nuraeni (Journal of Educational Sciences, 2026)
Limited critical thinking skills and low participation in biology learning often result in fragmented and less meaningful conceptual understanding. This study aimed to evaluate the effectiveness of a mind map-based constructive collaborative approach in improving students' critical thinking skills and participation in learning the human reproductive system. A quasi-experimental study employing a non-equivalent control group pretest–posttest design was conducted with 72 eleventh-grade high school students. Data were collected using a critical thinking test, the Student Engagement Scale, classroom observations, and analyses of collaborative mind maps. The findings revealed that students in the experimental group achieved greater improvement in critical thinking skills than those in the control group, with N-Gain scores of 0.687 and 0.544, respectively, and the difference was statistically significant (Mann–Whitney, p < 0.001). Student participation also increased more substantially in the experimental group, particularly in the agentic and cognitive engagement dimensions. Spearman correlation analysis indicated a significant positive relationship between critical thinking skills and student participation (rₛ = 0.392, p = 0.001). Qualitative findings further demonstrated improvements in conceptual integration, scientific argumentation, and active engagement. These findings suggest that a mind map-based constructive collaborative approach effectively promotes higher-order thinking skills and active participation in biology learning.